(untitled) (Kolaborasi : Jurnal Administrasi Publik, 2022)
Budget execution is the critical stage in the management of public finances. One of the performance indicators of budget implementation is the quality of state expenditure payments. In this case, the accuracy of the spending unit in completing bill payments is part of the quality of state expenditure payments. Currently, there are several spending units who experience delays in completing their bill payments. This study aims to determine the factors that affect the delay in the settlement of the bill. This study uses a quantitative method with the Explanatory Factor Analysis (EFA) method to identify variables that affect the delay in bill payments for all spending units at the Jakarta V State Treasury Office in 2019-2021. The results showed that information technology, supplier behavior, state treasury services, human resource capability, and external motivation affected the delay in payment of state expenditures. The results of this study also complement previous study which found that supplier indiscipline and organizational structure are variables that affect delays in state expenditures payment. The role of organizational support in spending unit will a trigger for improving the quality of state expenditure payments in spending unit.